Chalcogenide : carbon nanotubes and graphene composites - Singh, Abhay Kumar, 1976-; Jen, Tien-Chien, 1959- (Boca Raton, FL ; Oxon : CRC Press, 2021)
"This book mainly focused on the emerging chalcogenide systems and their composites with the carbon nano tubes and graphene composites. Including crystalline/polycrystalline, nnao crystalline chalcogenide systems with carbon nano tubes and graphene composites in introductory manner, while, an extensive attention will be paid to amorphous chalcogenide systems - carbon nano tubes and graphene composites"--
Basic of the chalcogenides -- Glass formation and structural modification in glasses -- Introduction of carbon nanotubes -- Introduction of graphene -- Chalcogenide systems : CNTs nanocomposites -- Chalcogenide systems -- graphene composites -- Applications of the chalcogenide systems-CNTs.
OCLC-licensed vendor bibliographic record.
Keywords: Chalcogenides; Nanocomposites (Materials); Carbon nanotubes; Graphene; SCIENCE / Nanostructures; SCIENCE / Solid State Physics; SCIENCE / Life Sciences / General